A MATERIAL DESCENT INTO DIGITAL MEDIA - Allen-Robertson, James (AoIR Selected Papers of Internet Research, 2015)
Utilising technical manuals and archives this paper historically and materially situates the Hard Disk drive as a material foundation for contemporary digital media. Using Foucault’s concept of ’descent’ as a historical but also material unpicking of the present, the paper descends into the Hard Disk Drive, the Gramophone and Phonograph, Magnetic Tape and Optical Media. This descent is used to provide a historical perspective on the way in which fundamental material factors constrain, influence and encourage particular uses of digital media. Specifically the descent demonstrates how the Hard Disk drive’s operation plays a role in the affordances of digital media and how these affordances are prefigured in older media technologies. The paper hopes to demonstrate that, given the right conceptual frameworks, we can historically and materially ground our understanding of digital media, understand its uses and consequences from a material foundation, and make sense of our most prominent contemporary media form.